Brand value and brand equity: essence, difference and relationship - Hurzhii, Nataliia (Management and Entrepreneurship: Trends of Development, 2022)
The article is devoted to the disclosure of the essence of the concept of brand capital, brand value, the main approaches to their definition are characterized, the distinguishing features of each category are given, but in their relationship. The criteria that determine the value of the brand from the point of view of the consumer and from the point of view of the producer are presented. The main approaches to the components of the brand model are considered. The main components of brand capital are revealed - value, power and image. When evaluating brand capital, it is suggested that managers take into account the stages through which the consumer passes in his relationship with the brand.In the course of the research, definitions of brand equity as an economic category and enterprise asset were given; its main elements are identified; the main principles of brand equity management are characterized, which will contribute to the improvement of the effectiveness of brand management.JEL Classification: А10, R11, D11.